Analisis Hukum Keabsahan Sertifikat Hak Atas Tanah Yang Terbit Tanpa Akta Pejabat Yang Berwenang: (Studi Kasus Putusan Hakim Pengadilan Negeri Raba Bima Nomor : 13/Pdt.G/2020/PN.RBi) - Azizah Dyan Lestari; Shinta Andriyani (Fakultas Hukum Universitas Mataram, 2022)
The purpose of this research was, first, to determine and understand the validity of land rights certificates issued without a certificate of land deed official (Pejabat Pembuat Akta Tanah or PPAT); second, to learn and understand the judge's considerations on land rights certificates without a land deed official in verdict of the Raba Bima District Court Number 13/PDT.G/2020/PN.RBI, how the law decides right or wrong, with a statutory approach, conceptual approach, and case approach. Data was collected by using sources of primary, secondary and tertiary legal materials. The technique of obtaining legal materials was conducting a literature study by examining various legal materials related to the subject matter. Furthermore, legal material was conducted using a card system, either with a summary card; quote card; and review cards. The data was compiled in a qualitative descriptive matter, problem solving procedures studied by describing the data obtained both primary and secondary data. Based on this research, according to law, Certificates issuedas an evidence of land rights without an authority of PPAT, are legal. And the judge's opinion in case number 13/Pdt.G/2020/PN.Rbi was invalid, illegitimate and not legally binding, it also cannot be justified by the law because the issuance of land rights certificates is not only proven by the existence of the notarial deed of sale which issued before PPAT, but can also use other evidence which is the Head of National Land Agency (Badan Pertanahan Nasional or BPN). It has the level of validity that is considered sufficient to register the transfer of land rights.